CD19 CAR-T in relapsed t(8;21) AML: a single-center prospective phase II clinical trial - Jia Yin; Qing-Ya Cui; Hai-Ping Dai; Chang-Ju Qu; Zheng Li; Li-Qing Kang; Wei Cui; Xiao-Peng Tian; Xia-Ming Zhu; Lei Yu; De-Pei Wu; Xiao-Wen Tang (Journal of Hematology & Oncology)
Abstract Approximately 78.3% of patients with t(8;21) acute myeloid leukemia (AML) express CD19, making it a potential target for chimeric antigen receptor (CAR)-T cell therapy focused on CD19. This prospective phase II trial (NCT03896854) evaluated the safety and efficacy of CD19 CAR-T cell treatment in 10 relapsed CD19-positive t(8;21) AML patients. This study enrolled eight patients with hematologic and two with molecular relapsed AML. The median bone marrow blast percentage was 12.4% (0.1–50.2%), and the blasts exhibited a median CD19 positivity of 55.7% (22.6–97.1%). Genetic profiling revealed TP53 alterations (n = 1), KIT (n = 3) and FLT3-ITD (n = 1) mutations. After lymphodepletion with fludarabine and cyclophosphamide (FC), 5–20 × 106 cells per kilogram of CAR-T cells were administered. All patients experienced grade 3 or higher hematologic toxicities following tumor-reduction chemotherapy and the FC regimen, which were managed for a median of two weeks after CAR-T treatment. Non-hematological toxicities were mild and reversible. Eight patients presented with mild (grade 1–2) cytokine release syndrome (CRS), and one experienced grade 3 CRS. The immune effector cell-associated neurotoxicity syndrome was not observed. All patients achieved complete remission (CR) after CAR-T, with 60% achieving a molecularly MRD-negative CR. RUNX1::RUNX1T1 fusion transcript levels demonstrated a median 2.5-log reduction (range: 0.7–4.5 log; P = 0.002). At a median follow-up of 64.6 months (range: 11.2–88.8 months), the median overall survival and leukemia-free survival were 11.6 and 3.8 months, respectively. The 12-month cumulative incidence of relapse was 53.3%. These findings indicated that CD19 CAR-T was a safe and effective option for relapsed CD19-positive t(8;21) AML.